Implications of the gut microbiome in spinal cord injuries - Jeyaraman, Naveen; Jeyaraman, Madhan; Dhanabal, Priya; Ramasubramanian, Swaminathan; Ambrosio, Luca; Vadalà, Gianluca; Muthu, Sathish (Frontiers in Surgery, 2025)
Spinal cord injuries (SCIs) present complex challenges in medical treatment and rehabilitation, profoundly affecting the patient's physiological and neurological status. Emerging research on the gut microbiome has unveiled its potential role in influencing SCI outcomes and recovery. The gut microbiome undergoes significant changes following SCIs, which influence systemic inflammation and increase susceptibility to secondary complications, such as infections and chronic pain. These effects are linked to altered permeability, immune system dysregulation, and activation of the gut-brain axis, which represent promising therapeutic targets for the treatment of these conditions. Insights into the mechanisms underlying these effects were explored, highlighting the roles of microbial-derived metabolites like short-chain fatty acids, which have been shown to possess anti-inflammatory properties and support neuroprotective responses. The implications of these findings are significant, suggesting that interventions aimed at modulating the gut microbiome, such as the use of probiotics, prebiotics, and faecal microbiota transplantation, could complement existing SCI treatments and support recovery processes. This review aims to synthesise current knowledge on the interplay between the gut microbiome and SCIs, exploring how this relationship can influence immune modulation, inflammation, and neuroplasticity, thereby affecting recovery trajectories and the necessity for interdisciplinary research approaches that integrate neurology, microbiology, and nutrition to develop holistic, effective treatment strategies for SCI patients.